The Increasing of Employee Retention in The Hotel Industry: Diagnosing the Effect of Work-Life Balance - Firza Tullah Aufa; Febbi Ari Istiqomah; Nur Fadillah; Feri Ferdian (PROGRAM STUDI PARIWISATA SYARAH, FAKULTAS EKONOMI DAN BISNIS ISLAM, UNIVERSITAS ISLAM NEGERI MATARAM, 2023)
Purpose: This paper investigates the influence of job engagement and work-life balance on increasing employee retention in the Hotel Industry. Method: The study used quantitative research with a causal associative approach. The population in this study was 63 employees of Natra Bintan Resort. 40 respondents were successfully collected using simple random sampling techniques. Data was obtained through a structured questionnaire and supplemented with a desk review of the literature. The proposed model is analyzed through the Smart PLSS assessment. Result: The result of this study found that there is a significant influence on the significant work engagement path. Meanwhile, there is an insignificant influence of the work-life balance path on employee retention. Job engagement and work-life balance are predictors of employee retention in the hospitality industry. Contribution: The contribution of this study is manifestly found as a significantly increasing employee retention which will give a big impact on the Hotel Industry. The company is expected to pay attention to the relationship between employees and superiors about work-life balance and job engagement and employees get complete information about the requirements for occupying a position. The theoretical contribution of this research lies in its exploration of the influences of work-life balance and job engagement on employee retention within the hotel industry. By empirically testing these relationships and differentiating their impacts, the study provides valuable insights for both academia and the practical management of human resources in the hospitality sector